Simulation, implementation and measurement of a microstrip antenna - Wee, Nigel (Nanyang Technological University, 2023)
Microstrip patch antennas are small and compact, making them ideal for applications where size is a constraint. Single-ended patch antennas are the most common. The goal of this project is to design, simulate and measure a differentially-driven aperture coupled microstrip patch antenna. Literature review is done to gain an understanding of antennas, then the antenna is designed and simulated to satisfaction. Then the antenna is manufactured and measured. Due to time constraints, the antenna was ultimately not manufactured.